Implementation of the Turbo Boyer Moore Method in Searching Thesis Titles at the Website-Based Faculty of Economics - Gustian Febri Syah Putra; Juju Jumadi; Abdussalam Al Akbar (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
Every year, students are required to complete a final project in the form of a thesis as one of the graduation requirements. However, in determining a thesis title that is relevant to the chosen scientific field, students often experience difficulties. The number of thesis titles available in libraries and websites can confuse students in choosing the right title. One method that can be used to achieve this goal is the Turbo Boyer-Moore pattern search method. Turbo Boyer-Moore is one of the efficient pattern matching algorithms to search for certain words or phrases in text. From the results of the tests carried out, it can be concluded that the implementation of the designed program in searching and detecting the same title with a similarity percentage.